Assessing post-game emotions in soccer teams: The role of distinct emotional dynamics. Issue 6 (3rd June 2022) - Rumbold, James L.; Newman, James A.; Foster, David; Rhind, Daniel J. A.; Phoenix, Jack; Hickey, Lorcan
ABSTRACT: This study examined the relationships between team ( n = 10) and player post-game emotions following two consecutive games. In addition, the relationship between emotional contagion susceptibility and player post-game emotions was assessed. Applying an experience sampling methodology, male amateur and semi-professional soccer players ( N = 114, M age = 25.46 years, SD = 9.24) completed a sport emotion questionnaire shortly after the conclusion of two competitive games. Participants also completed a dispositional emotional contagion questionnaire prior to post-game data collection. Multilevel regressions revealed that teams' collective post-game emotions were strongly associated with players' post-game emotions, after accounting for within- (e.g. time, game outcome) and between-person (e.g. formal leaders, emotional contagion susceptibility) differences. In addition, partial support was found to indicate that emotional contagion susceptibility was associated with players' post-game emotions. In this context of soccer, the findings suggest that collective emotions following a game are more indicative of individual players' emotions than an individual's general tendency to mimic the emotions of others. From an applied perspective, the findings demonstrate the importance of coaches and players being mindful of the team's emotional climate after a game and the impact it may have on players, especially when that climate is negative. Highlights: We assessed the relationship between soccer team ( n = 10) and player ( N = 114) post-game emotions. We also assessed how emotional contagion susceptibility was linked to post-game emotions. Multilevel regressions revealed that team's collective post-game emotions are more indicative of players' post-game emotions than a player's emotional contagion susceptibility.